The Technological Quality of Barley Lines Selected from the First Cycle of Participatory Breeding in Algeria - MOHAMED, ZAIRI; Noureddine, Menadi; BENABDERRAHMANE, MOKHTAR; BENALI, MOHAMMED; HAMOU, MIMOUNE; LABDI, MOHAMED (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
AbstractThis paper aims at investigating the technological quality of barley lines selected from the first cycle of participatory plant breeding (PPB) conducted in Algeria, and compared them with two varieties widely grown in Algeria (Saida183 and Rihane-03). Several physicochemical and technological parameters were evaluated: thousand kernel weight (TKW), hectoliter weight (HW), protein content, ash content (ash), yield in semolina and in couscous, and the culinary quality of the couscous. Couscous from all entries were appreciated and considered as satisfactory. The selected lines showed a better adaptation to the environment. This selection allows us to develop and to make available to farmer’s varieties adapted to local conditions (arid) with promising quality for a common food. The participatory selection was an effective tool to improve barley yield and yield stability, as well as the quality of barley products confirming the usefulness of the participatory model. The results showed the possibility of making good quality couscous with barley, which may open a new potential market for an old cereal.  Keyword: Adaptation; Participatory Plant Breeding; Consumer Preference; Couscous